Podstawowe kryteria tworzenia powiatów - Budner, Waldemar; Kaczmarek, Tomasz; Matykowski, Roman (Wydział Prawa i Administracji UAM, 1993)
The article discusses basic criteria of re-activating the district (poviat) structure: efficient administration, efficient satisfaction of the needs of the population, social ties and acceptance, the principle of coincidence of the borders of districts (poviats) and the division of special administration. In determining the seats and borders of districts (poviats), a starting point is the principle of the key role, based on the concep of central places and nodal regions. The problems of the reconstruction of t he district (poviat) structure are examined in the context of social and political conditioning of t he public administration reform in Poland.
Basic criteria of creating the districts